Developing spirituality - an equal right of every child? - Stockinger, Helena (International journal of children's spirituality, 2019)
Children's spiritual development is influenced by those with whom they interact and by the world around them. An important context for young children is the kindergarten, which has a high level of responsibility for their (spiritual) education. At kindergarten children encounter people with different religious and spiritual attitudes, which may be fundamental to the development of their own spirituality. Research results regarding how two kindergartens in Austria deal with this diversity and how children address it are summarized. One result of this qualitative ethnographic research project is that, depending on their religion, children have different opportunities to develop their spiritual communication and spirituality based on religious traditions and rituals. Developing kindergartens in line with the metaphor of safe spaces where diversity is recognized and discussed can contribute to the creation of equal opportunities for children's spiritual development.